INTERNALIZING ISLAMIC VALUES IN ELECTROCHEMISTRY LEARNING - Subarkah, Cucu Zenab; Rahmawati Sg, Risa; Dalli, Ajeng (Jurnal Pendidikan Islam, 2016)
The purpose of this paper is to describe a potential way of integrating the knowledge of electrochemistry with a story in the Al-Quran particularly in the sura of Al-Kahfi, verse 83-96. The story tells about an implicit understanding of the concept of electro chemistry. Having the story in the learning of electrochemistry is aimed to internalizing the spirit of Islam in the learning of electro chemistry. Using a classroom action research, this study involved 95 students who are taking the course of Basic Chemistry 2. This study used three instruments, namely: observation sheet of students activity, observation sheet of students attitute, and self-assessment questionnaire. Based on the data, the study found that students were considerably active in each stage of the learning process with the average of activitiy is 78% (good). With regards to attitude, only aspect of responsibility that was not well appeared while the aspects of religious curiosity, cooperative, and communication relatively presented Â